A new species, Microphysogobio wulonghensis (Teleostei: Cypriniformes: Cyprinidae), from Shandong Province, China - Xing, Ying-Chun; Zhao, Ya-Hui; Tang, Wen-Qiao; Zhang, Chun-Guang (Zootaxa, 2011)
Microphysogobio wulonghensis sp. nov. is described based on 15 specimens collected from the Wulonghe River in Laiyang County of Shandong Province in eastern China. The new species can be distinguished from all congeners by the combination of the following characteristics: upper lip with one row of well-developed and compressed triangular papillae; two lateral pads of lower lip well-developed, contacting each other behind medial pad; two-thirds of area between pectoral-fin origin and pelvic-fin origin scaleless.